Pendampingan Metode Karimah untuk Meningkatkan Kemampuan Membaca Al-Qur’an Anak Usia Dini di TPA Darul Rahman Palangka Raya - Rizqi, Muhammad; Majidi, Muhammad Wahid; Surawan, Surawan; Rukaiyah, Rukaiyah (Universitas Pahlawan Tuanku Tambusai, 2025)
The ability to read the Qur'an is an important foundation for Muslims, especially if it is instilled from an early age. However, there are still many early childhood children who face difficulties in reading the Qur'an properly and correctly. This study aims to improve the ability to read the Qur'an of early childhood at TPA Darul Rahman Palangka Raya through the assistance of the Karimah method. The Karimah method, which emphasizes systematic and structured teaching of Arabic letters and tajweed, is considered effective for beginners. This research uses the Action Research method with the stages of planning, action, observation, and reflection. The research subjects were 7 students of class A at TPA Darul Rahman. The results of the observation showed that the main problem lies in the lack of emphasis on the short length of the reading, makharijul huruf, and the application of tajweed rules. Through intensive assistance for 5 meetings, there was a significant improvement in the participants' ability to read the Qur'an. The Karimah method proved to be effective due to its simple approach, focus on concise and structured exercises, and interesting presentation of materials. This program is very much needed by people who want to learn to read the Qur'an in a short time.